Research objectives to fill knowledge gaps in African swine fever virus survival in the environment and carcasses, which could improve the control of African swine fever virus in wild boar populations - Nielsen, Søren Saxmose (EFSA J, 2021)
The European Commission requested that EFSA provide study designs for the investigation of four research domains according to major gaps in knowledge identified by EFSA in a report published in 2019: i) the patterns of seasonality of African Swine Fever (ASF) in wild boar and domestic pigs in the EU; ii) the epidemiology of ASF in wild boar; iii) survival of ASF virus (ASFV) in the environment and iv) transmission of ASFV by vectors. In this Scientific Opinion, the third research domain on ASFV survival is addressed. Nine research objectives were proposed by the working group and broader ASF expert networks, such as ASF stop, ENETWILD, VectorNet, AHAW network and the AHAW Panel Experts. Of the nine research objectives, only one was prioritised and elaborated into a general protocol/study design research proposal, pertaining ASFV survival in feed and bedding. To investigate the survival of ASFV in feed, bedding and roughage, laboratory survival studies are proposed. To investigate possible risk mitigation measures, proof‐of‐concept approaches should be investigated.